Speaking anxiety among English majors: A mixed-methods study of psychological, linguistic, and environmental barriers - Sukmawati, Ria; Maghfiroh, Ana; Nimasari, Elok Putri; Yulianti, Dwiana Binti; Frossard, Rafael Altoé (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to: (1) identify the psychological causes of speaking anxiety among English Education students; (2) examine the influence of environmental factors, such as classroom dynamics and peer interaction, on students’ speaking confidence; and (3) explore linguistic challenges, including limited vocabulary and grammatical competence, that hinder speaking fluency. The study employed a mixed-methods design with an explanatory sequential approach, combining quantitative survey data from 30 students with in-depth interviews involving three selected participants. The findings revealed that fear of making mistakes (M = 3.70) and concerns about pronunciation (M = 3.50) were the primary sources of speaking anxiety. Qualitative results indicated that linguistic challenges were closely linked to psychological factors and shaped by classroom dynamics. While previous studies have highlighted peer pressure as a major source of anxiety, this study found that peer influence tended to be neutral within a supportive classroom environment. These findings suggest that speaking anxiety is shaped by the interaction of psychological, linguistic, and environmental factors. Therefore, effective interventions should adopt a holistic approach that integrates confidence-building, supportive teaching practices, and communicative activities.